2015
DOI: 10.1111/jdv.13170
|View full text |Cite
|
Sign up to set email alerts
|

Association of psoriasis and/or psoriatic arthritis with autoimmune diseases: the experience of two Italian integrated Dermatology/Rheumatology outpatient clinics

Abstract: The new concept of psoriatic disease, focusing on genetic and molecular aspects which are at the basis of the pathogenesis of psoriasis and its related manifestations, extended the traditional idea of a disease confined to skin and joints. In this context, the multidisciplinary assessment of patients in the combined Dermatology/Rheumatology outpatient clinics would allow to identify early clinical and laboratory abnormalities not limited to skin and joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Psoriatic arthritis is a chronic inflammatory arthropathy typically associated with psoriasis. Psoriasis is a complex multifactorial disease related to a combination of genetic, environmental and immunological factors, involving both innate and adaptive immune systems (2,3). Keratinocytes play a key role in the recruitment and activation of T cells in psoriatic lesions and T cells are fundamental in the maintenance of the u s e festations.…”
Section: N Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriatic arthritis is a chronic inflammatory arthropathy typically associated with psoriasis. Psoriasis is a complex multifactorial disease related to a combination of genetic, environmental and immunological factors, involving both innate and adaptive immune systems (2,3). Keratinocytes play a key role in the recruitment and activation of T cells in psoriatic lesions and T cells are fundamental in the maintenance of the u s e festations.…”
Section: N Psoriasismentioning
confidence: 99%
“…Such changes are associated with striking variations in the keratin profile expressed by keratinocytes, with overexpression of keratin 16, indicating hyperproliferation of keratinocytes (9). Immunohistochemistry studies provide evidence that psoriatic lesions contain increased numbers of T cells that are CD3+ CD2+ CD45RO+ CLA+, with a subset having activation markers CD25, HLADR, and CD27; several CD4+ T cells produce IFN-gamma, IL-17, and IL-22; some CD8+ cells and an increased number of BDCA-1 CD11c+ inflammatory dermal dendritic cells (2,3,10).…”
Section: Reviewmentioning
confidence: 99%
“… 7 , 8 Few epidemiologic studies found that patients with psoriasis are at greater risk of AA development. 9 , 10 It is estimated that patients with psoriasis have a 2.5-fold higher risk of AA development and are more likely to have at least 1 other autoimmune disease (odds ratio [OR], 1.6; confidence interval [CI], 1.5-1.7) or even 2 other autoimmune diseases (OR, 1.9; CI, 1.6-2.4). 9 A recent retrospective study found that vitiligo was the most frequent skin autoimmune disease associated with psoriasis, followed by AA and chronic urticaria.…”
Section: Introductionmentioning
confidence: 99%
“… 9 A recent retrospective study found that vitiligo was the most frequent skin autoimmune disease associated with psoriasis, followed by AA and chronic urticaria. 7 , 10 The most frequent association seems to be scalp psoriasis and AA. 7 , 9 Although some investigators found that psoriatic arthritis (PsA) might represent a protective factor, 9 , 10 others found that patients with AA are more frequently affected by either psoriasis or PsA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation